[PP.19.18] ASSOCIATION OF ARTERIOSCLEROSIS AND/OR ATHEROSCLEROSIS WITH HYPERTENSIVE TARGET ORGAN DAMAGES IN THE COMMUNITY-DWELLING ELDERLY CHINESE: THE NORTHERN SHANGHAI STUDY. (September 2017) - Fan, X.; Xu, Y.; Zhang, Y.; Lu, Y.; Xiong, J.; Yu, S.; Chi, C.; Bai, B.; Teliewubai, J.; Zhou, Y.
Abstract : Objective: Cardiovascular events and mortality are tightly associated with vascular abnormalities. There are two types of modifications in vascular structure, namely arteriosclerosis and atherosclerosis, which coexist in many patients with cardiovascular diseases. However, it remains unclear whether their combination may lead to worse status in those patients. We therefore aimed to investigate the association of arteriosclerosis and/or atherosclerosis with hypertensive target organ damages (TODs), within a framework of cardiovascular risk assessment in a community-dwelling elderly cohort. Design and method: From June 2014 to August 2015, a total of 1599 community- dwelling elderly subjects (age >65 years old) located in the northern Shanghai were recruited. Vascular measurements, such as carotid-femoral pulse wave velocity (cf-PWV), ankle-brachial index (ABI) and carotid plaque, were conducted on each participant, and arteriosclerosis was defined as cf-PWV > 12 m/s, while atherosclerosis was defined as with carotid plaque or ABI < 0.9. Within the framework of comprehensive cardiovascular examinations, risk factors were assessed, and asymptomatic TODs were evaluated by measuring participants' left ventricular mass index (LVMI), peak transmitral pulsed Doppler velocity / early diastolic tissue Doppler velocity (E/Ea), urinary albumine-creatinine rate (UACR), evaluate glomerular filtration rate (eGFR). Results: Age, body mass index, smoking status, systolic blood pressure and fasting plasma glucose were significantly different among participants with or without arteriosclerosis and/or atherosclerosis (p < 0.02). Although LVMI, E/Ea and eGFR were significantly different among subjects with or without arteriosclerosis and/or atherosclerosis (P for trend < 0.02), in full adjustment model, only E/Ea significantly differed among subjects with or without arteriosclerosis and/or atherosclerosis (P for trend = 0.023). Moreover, E/Ea was significantly different between participants with arteriosclerosis or atherosclerosis and those without (P = 0.045), while there was no significant difference between participants with arteriosclerosis and atherosclerosis and those without (P = 0.28). Similar results were obtained in the multivariate logistic regression of left ventricular diastolic dysfunction (LVDD). With similar adjustment, LVDD was significantly associated with atherosclerosis (P = 0.01) but not with arteriosclerosis (P = 0.99). Conclusions: In the community-dwelling elderly Chinese, among hypertensive target organ damages, LVDD was significantly associated with atherosclerosis but not with arteriosclerosis, and their combination does not worsen patients' LV diastolic function. Figure. No caption available.